Strategi Memperlambat Usia Menopause Di Posyandu Posyandu Lansia Kabupaten Rokan Hulu. - Andria, Rika Herawati, Heny Sepduwiana, (Jurnal Martenity and Neonatal, 2014)
It is also found in Indonesia, it begins from 47 years to 45 years that is caused by some aspects. The Objective of this study is to determine the aspects that relates to the age of menopause at Older Hospital in Rokan Hulu on 2013. The method of this study is Quantitative Study Cross Sectional study, its sample are 763 postmenopausal women, by using a stratified random sampling technique. Data is analized by using Univariate, Bivariate, T test and product moment correlation, and multivariate multiple regression tests. The result is, there are some variables that relates with age of menopause. They are smoking, income, sport, age last birth, number of children, contraception, history of education, history of alcohol consumption and menarche. It can be found in the data; menopausal age = 39.16, - 0.140 cigarette consumption+ 3,39 income, + 0764 sport +0026 Age last birth, + 0.161 Number of Children, + 3,628 Contraception, +0075 Education History + 6,662 History of Alcohol Consumption - 0.109 Menarche. The greatest effect Variable are cigarete consumption, income, sport, number of children, contraceptive uses, history of alcohol consumption, the last age birth, menarche, and the lowest education. With R Â² is known that 67.7% menopausal age variation can be explained by those independent variables and 32.3% other aspect that is not conducted in this research. The strategies for decreasing woman menopausal age are stoping to consume cigarete, doing home industry, doing sport regularly at least 30 minute per day, programming healthy life, avoiding stress, spacing birth time by using hormonal contraception, birthing in healthy reproduction age in 20-35 years, avoiding to consumee alcohol, giving the higherst education and improving their knowledge from newspaper, television and also consuming good nutrition to children from early age.